Analysis of Human Resource Planning and Work Motivation in Maintaining Seaweed Productivity - Nasya Soraya YusufYusuf; Zainiyatul Afifah; Mudji Kuswinarno (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study examines the role of Human Resources (HR) planning and work motivation in increasing seaweed farming productivity in Sumenep, Madura. The research method uses a qualitative approach with data collection through in-depth interviews, participant observation, and documentation. The main informant is the head of the seaweed farming group in Pagarbatu Village, Saronggi District, Sumenep. The data collected were analyzed using thematic analysis techniques. The results of the study indicate that good HR planning, including skills training and maintaining the welfare of group members, contributes significantly to increasing productivity. In addition, high work motivation, influenced by the fulfillment of physiological needs, security, and social appreciation, also plays an important role in increasing the work spirit of seaweed farmers. Although the farmer group does not have a formal HR plan, they apply effective principles in developing the capacity of its members. This study is expected to provide insight into the development of HR planning and work motivation in the seaweed farming sector, as well as encourage increased productivity and welfare of coastal communities.